ANALYSIS OF NOISE IMPACT FROM SULTAN SYARIF QASIM II PEKANBARU INTERNATIONAL AIRPORT ACTIVITIES - Abdul Kudus Zaini; Nabila Dwi Putri; Harmiyati Harmiyati (International Journal of Engagement and Empowerment, 2021)
The more developed a province area, the more developed means of transportation in the city. Especially airplanes. This transportation is increasingly needed; various types of aircraft connect airports throughout the International. The purpose of the study was to determine the impact caused by the Noise of Sultan Syarif Kasim II Airport activities on the community around the airport area, then compare the noise level in settlements and airports with the Ministry of Environment Decree No. 48 of 1996 of the noise level quality standard. By using a Sound Level Meter (SLM). The research was conducted for three days, the first day was conducted in the southern residential area, the second day was conducted in the northern residential area, and the third day the research was conducted in the airport area. The results showed that the northern housing 73.43 dBA and the southern housing 75.69 dBA exceeded the noise level quality standard set at 55 dBA. The highest exposure duration was at the northern runway location, and the eastern runway noise exposure was only allowed for 3 hours. The Time Weight Average (TWA) or average daily Noise on the runway is 89.1 dBA, exceeding the standard that has been set, which is 85dBA, Kepmenaker No.51/1999), the maximum that workers can receive in one day of 8 working hours can only receive 85 dBA. Based on the research analysis results, it was found that Noise has disturbed the comfort of residents. It is better if the airport's location must have land use moved to a new location far from residents' settlements.